Evaluating the impact of indigenous foods on stunting prevention in rural Indonesian communities - Septi Marlinton; Sulistyaningsih Sulistyaningsih (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Stunting remains a significant public health concern in Indonesia, underscoring the potential for utilizing local food resources as a key strategy for effective nutritional improvement and prevention measures. This review examined the impact of innovative applications of local foods on enhancing children's nutrition, emphasizing diverse food varieties, methodological approaches, and their efficacy in reducing stunting rates across the country. The research employed a scoping review methodology following the PRISMA-ScR guidelines and PEO framework. Relevant literature from PubMed, ScienceDirect, Crossref, and Google Scholar published between 2013 and 2023 was selected based on inclusion criteria that emphasized the utilization of local foods for stunting prevention, open access, and availability in English or Indonesian. Non-empirical articles were excluded from the review, and the screening procedure involved evaluating abstracts and conducting a full-text analysis using Covidence. The validity of the studies was assessed through qualitative, quantitative, and mixed-methods data analysis utilizing tools developed by the Joanna Briggs Institute (JBI). This review revealed that innovative local food products, such as floss made from snakehead fish and chips created from locally sourced carbohydrates, have a significant positive impact on children's nutritional health. These foods are rich in essential proteins and micronutrients that contribute to improvements in children's weight and height and enhance overall nutrient consumption, thereby aiding in the prevention of stunting. In conclusion, the incorporation of snakehead fish floss and fish flour proved to be effective in enhancing the nutritional status of children with stunting, as demonstrated by mean weight gain of 0,5 kg and a height increase of 2 cm over 30 days.